On positive solutions of one class of evolutionary inclusions of the subdifferential type - Kapustyan, O. V.; Shklyar, T. B. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
Sufficient conditions of the existence of a nonnegative solution are obtained for an evolution inclusion of subdifferential type with multivalued non-Lipschitz perturbation. Under the additional condition of dissipativity, the existence of the global attractor in the class of nonnegative functions is proved.